From Salt to Stroke—Evaluation of a Media Campaign for Sodium Reduction in Philadelphia - Klassen, Ann C.; Sood, Suruchi; Summers, Amber; Perera, Udara; Shuster, Michelle; Lopez, Jessica P.; McCord, Andrea; Stokes, Jared; White, Joann; Wagner, Amanda (Frontiers in Public Health, 2021)
Excess dietary sodium contributes to the burden of chronic disease, including cardiovascular disease and stroke. Media-based health education campaigns are one strategy to raise awareness among populations at greater risk for stroke, including African Americans. During 2014–2015, the Philadelphia Department of Public Health conducted a health education campaign using radio, print news, and transit ads, to promote awareness of the link between dietary sodium, hypertension and stroke, and encourage reduced consumption of high sodium foods. Using a repeated cross-sectional design, street intercept surveys were conducted with 400 Philadelphia residents representing the campaign's priority audience (African Americans ages 35–55) before and 6–13 weeks after the campaign, to evaluate both process (campaign exposure) and impact (recall of key health messages). Thirty percent of post-campaign respondents reported familiarity with one of the most engaging radio spots, and 17% provided accurate unaided recall of its key content, with greater recall among older respondents and frequent radio listeners. Forty-one percent of post-campaign respondents named stroke as a consequence of excess salt consumption, compared to only 17% of pre-campaign respondents, with greater awareness of the salt-stroke connection among those accurately recalling the radio spot from the campaign. Results suggest that priority populations for sodium reduction can be effectively reached through radio and transit campaigns. From a pragmatic perspective, street intercept surveys may offer one low resource strategy for evaluating public health education campaigns conducted by local health departments, especially among urban populations.